Estimates of forest biomass in the Brazilian Amazon: New allometric equations and adjustments to biomass from wood-volume inventories - Nogueira, Euler Melo; Fearnside, Philip Martin; Nelson, Bruce Walker; Barbosa, Reinaldo Imbrozio; Keizer, Edwin Willem Hermanus (Forest Ecology and Management, 2008)
Uncertainties in biomass estimates in Amazonian forests result in a broad range of possible magnitude for the emissions of carbon from deforestation and other land-use changes. This paper presents biomass equations developed from trees directly weighed in open forest on fertile soils in the southern Amazon (SA) and allometric equations for bole-volume estimates of trees in both dense and open forests. The equations were used to improve the commonly used biomass models based on large-scale wood-volume inventories carried out in Amazonian forest. The biomass estimates from the SA allometric equation indicate that equations developed in forests on infertile soils in central Amazonia (CA) result in overestimates if applied to trees in the open forests of SA. All aboveground components of 267 trees in open forests of SA were cut and weighed, and the proportion of the biomass stored in the crowns of trees in open forest was found to be higher than in dense forest. In the case of inventoried wood volume, corrections were applied for indentations and hollow trunks and it was determined that no adjustment is needed for the form factor used in the RadamBrasil volume formula. New values are suggested for use in models to convert wood volume to biomass estimates. A biomass map for Brazilian Amazonia was produced from 2702 plots inventoried by the RadamBrasil Project incorporating all corrections for wood density and wood volume and in factors used to add the bole volume of small trees and the crown biomass. Considering all adjustments, the biomass map indicates total biomass of 123.1 Gt (1 Gt = 1 billion tons) dry weight (aboveground + belowground) for originally forested areas in 1976 in the Brazilian Legal Amazon as a whole (102.3 Gt for aboveground only) at the time of the RadamBrasil inventories, which were carried out before intensive deforestation had occurred in the region. Excluded from this estimate are 529,000 km2 of forest lacking sufficient RadamBrasil inventory data. After forest losses of 676,000 km2 by 2006 - not counting 175,000 km2 of this deforested area lacking RadamBrasil data - the estimated dry biomass stock was reduced to 105.4 and 87.6 Gt (aboveground + belowground and only above-ground). Thus, in 2006 the carbon storage in forested areas in Brazilian Amazonia as a whole will be around 51.1 Gt (assuming 1 Mg dry biomass = 0.485 Mg C). Biomass estimates by forest type (aggregated into 12 vegetation classes) are provided for each state in the Brazilian Legal Amazon. © 2008 Elsevier B.V. All rights reserved.
Keywords: Agglomeration; Biological Materials; Carbon; Curing; Deforestation; Forestry; Global Warming; Greenhouse Gases; Inventory Control; Land Use; Magnesium Printing Plates; Renewable Energy Resources; Simulated Annealing; Soils; Uncertainty Analysis; Wood; Allometric Equations; Allometric Relationships; Amazon Forest; Amazonia; Amazonian Forests; Biomass Equations; Biomass Maps; Biomass Models; Brazilian Amazons; Carbon Storages; Dry Biomasses; Dry Weights; Fertile Soils; Forest Biomasses; Forest Types; Forested Areas; Form Factors; Inventory Datum; Large-scale; Open Forests; Small Trees; Total Biomasses; Tropical Forest; Vegetation Classes; Wood Densities; Wood Volumes; Biomass; Allometry; Biomass; Carbon Sequestration; Equation; Estimation Method; Forest Inventory; Global Warming; Wood; Agglomeration; Biomass; Crowns; Forest Management; Greenhouse Gases; Inventories; Inventory Control; Wood; Amazonas; Amazonia; South America